Cubic Liquid Crystalline Nanostructures Involving Catalase and Curcumin: BioSAXS Study and Catalase Peroxidatic Function after Cubosomal Nanoparticle Treatment of Differentiated SH-SY5Y Cells - Rakotoarisoa, Miora; Angelov, Borislav; Espinoza, Shirly; Khakurel, Krishna; Bizien, Thomas; Angelova, Angelina (Molecules (Basel, Switzerland), 2019)
The development of nanomedicines for the treatment of neurodegenerative disorders demands innovative nanoarchitectures for combined loading of multiple neuroprotective compounds. We report dual-drug loaded monoolein-based liquid crystalline architectures designed for the encapsulation of a therapeutic protein and a small molecule antioxidant. Catalase (CAT) is chosen as a metalloprotein, which provides enzymatic defense against oxidative stress caused by reactive oxygen species (ROS) such as hydrogen peroxide (H2O2). Curcumin (CU), solubilized in fish oil, is co-encapsulated as a chosen drug with multiple therapeutic activities, which may favor neuro-regeneration. The prepared self-assembled biomolecular nanoarchitectures are characterized by biological synchrotron small-angle X-ray scattering (BioSAXS) at multiple compositions of the lipid/co-lipid/water phase diagram. Constant fractions of curcumin (an antioxidant) and a PEGylated agent (TPEG1000) are included with regard to the lipid fraction. Stable cubosome architectures are obtained for several ratios of the lipid ingredients monoolein (MO) and fish oil (FO). The impact of catalase on the structural organization of the cubosome nanocarriers is revealed by the variations of the cubic lattice parameters deduced by BioSAXS. The outcome of the cellular uptake of the dual drug-loaded nanocarriers is assessed by performing a bioassay of catalase peroxidatic activity in lysates of nanoparticle-treated differentiated SH-SY5Y human cells. The obtained results reveal the neuroprotective potential of the in vitro studied cubosomes in terms of enhanced peroxidatic activity of the catalase enzyme, which enables the inhibition of H2O2 accumulation in degenerating neuronal cells.
Keywords: Imaging, Three-Dimensional; reaktivní formy kyslíku; fish oil; Humans; catalase; Liquid Crystals; liquid crystalline nanoparticles; Catalase; cubosome; curcumin; BioSAXS; Nanostructures; lidé; Synchrotrons; peroxidatic activity of catalase; Polyethylene Glycols; kurkumin; kapalné krystaly; Reactive Oxygen Species; nanostruktury; Curcumin; katalasa; peroxid vodíku; Scattering, Small Angle; zobrazování trojrozměrné; maloúhlový rozptyl; synchrotrony; polyethylenglykoly; Hydrogen Peroxide